Post-partum hemorrhage: a multidisciplinary approach to ‘the golden hour’ quantum leadership and communication - Georges Yared; Jihad al Hasssan; Charlotte Al Hajjar; Kariman Ghazal (Future Science OA, 2023)
Background: Quantum leadership in postpartum hemorrhage (PPH) simulation training remains underexplored. Quantum leaders excel in PPH's chaotic settings, differing from traditional leaders. Aiming: To assess the impact of simulation training on quantum leadership skills in maternity teams. Research design: A quasi-experimental approach. Sample: 60 maternity professionals from Rafik Hariri University Hospital, Lebanon. Tools: Structured interviews, observational checklists, and a leadership skills scale. Results: Most participants had limited PPH simulation experience and showed an initial low proficiency. Post training, significant improvements were evident. Conclusion: Simulation training enhances quantum leadership in PPH management among maternity professionals.